Serum Pseudocholinesterase as a Biomarker in the Differentiation between Gastric Cancer and Benign Gastric Diseases - Shaqi, Maha Abdulhussain; Rijub-Agha, Anne Khazal Yaseen; Hussain, Ragad Jawad (AL-Kindy College Medical Journal, 2023)
Background: Worldwide gastric cancer is the fifth most common cancer with poor prognosis. In early stages, it is hard to distinguish gastric cancer from benign gastric diseases, resulting in delayed diagnosis. There is a need to develop a biomarker for differentiating between gastric cancer and benign gastric diseases. Serum cholinesterase is synthesized in liver and released into plasma, and it has an important role in oncogenesis.Objectives: To determine the correlation between serum cholinesterase activity and gastric cancer, in comparison to benign gastric diseases.Subjects and Methods: A case control study carried out at Medical City Directorate\ Gastroenterology, Hepatology Hospital, and at Oncology Teaching Hospital from April 2022 to September 2022. It involved 25 patients with gastric cancer and age matched 25 patients with benign gastric diseases. Serum cholinesterase activity was determined by a colorimetric method..Results: There was a significant difference in the mean level of serum cholinesterase between gastric cancer group (5339.28 U/L±1816) and benign gastric diseases group (7516.92 U/L±2351) with (P value